Using an intervention mapping approach for planning, implementing and assessing a community-led project towards malaria elimination in the Eastern Province of Rwanda. (December 2016) - Ingabire, Chantal; Hakizimana, Emmanuel; Kateera, Fredrick; Rulisa, Alexis; Den Borne, Bart; Nieuwold, Ingmar; Muvunyi, Claude; Koenraadt, Constantianus; Vugt, Michele; Mutesa, Leon; Alaii, Jane
Abstract Background Active community participation in malaria control is key to achieving malaria pre-elimination in Rwanda. This paper describes development, implementation and evaluation of a community-based malaria elimination project in Ruhuha sector, Bugesera district, Eastern province of Rwanda. Methods Guided by an intervention mapping approach, a needs assessment was conducted using household and entomological surveys and focus group interviews. Data related to behavioural, epidemiological, entomological and economical aspects were collected. Desired behavioural and environmental outcomes were identified concurrently with behavioural and environmental determinants. Theoretical methods and their practical applications were enumerated to guide programme development and implementation. An operational plan including the scope and sequence as well as programme materials was developed. Two project components were subsequently implemented following community trainings: (1) community malaria action teams (CMATs) were initiated in mid-2014 as platforms to deliver malaria preventive messages at village level, and (2) a mosquito larval source control programme using biological substances was deployed for a duration of 6 months, implemented from January to July 2015. Process and outcome evaluation has been conducted for both programme components to inform future scale up. Results The project highlighted malaria patterns in the area and underpinned behavioural and environmental factors contributing to malaria transmission. Active involvement of the community in collaboration with CMATs contributed to health literacy, particularly increasing ability to make knowledgeable decisions in regards to malaria prevention and control. A follow up survey conducted six months following the establishment of CMATs reported a reduction of presumed malaria cases at the end of 2014. The changes were related to an increase in the acceptance and use of available preventive measures, such as indoor residual spraying and increase in community-based health insurance membership, also considered as a predictor of prompt and adequate care. The innovative larval source control intervention contributed to reduction in mosquito density and nuisance bites, increased knowledge and skills for malaria control as well as programme ownership. Conclusion This community-based programme demonstrated the feasibility and effectiveness of active community participation in malaria control activities, which largely contributed to community empowerment and reduction of presumed malaria in the area. Further studies should explore how gains may be sustained to achieve the goal of malaria pre-elimination.